High-performance polyphenylene sulfide composites with ultra-high content of glass fiber fabrics. (1st October 2019) - Zhao, Liang; Yu, Yan; Huang, Hao; Yin, Xianze; Peng, Jiashun; Sun, Jiuxiao; Huang, Leping; Tang, Youhong; Wang, Luoxin
Abstract: In this work, the high strength and rigidity composites composed of ultra-high content of glass fiber fabrics (GFF) and polyphenylene sulfide (PPS) nonwovens were successfully fabricated by a facile thermo-compression lamination method. The mechanical property, wettability, crystalline behavior, rheological behavior and dynamic mechanical properties were systematically characterized. These results show that the optimum formula of 80 wt% GFF content (∼70 vol%) can achieve the best mechanical properties of the composite with excellent wettability among PPS and glass fibers. The tensile strength, fracture elongation, elastic modulus, flexural strength, flexural modulus, ILSS and un-notched impact strength can reach to 850.6 MPa, 10.5%, 910.5 MPa, 78.5 GPa, 67.4 MPa and 215.2 kJ/m 2, respectively, which are elevated by 108.8%, 38.2%, 52.8%, 82.6%, 230.4% and 136.5% in comparation to those of GFF/PPS composites with 60 wt% GFFs. The increasing interfacial layers and riveting effect among GFFs effectively prevent the crack propagation, which are the main reasons for the enhancing mechanical properties of PPS composites with ultra-high content GFF. It is established that the GFF/PPS composite fabricated in this work has the characteristic of the highest mechanical performance and the highest content of GFFs in comparison with the reported PPS-based composites. This GFF/PPS composite is an ideal substitute for traditional metal and GF/epoxy composites.